The Influence of Career Development and Transformational Leadership on Employee Performance - Edy Hartono; Aries Firmansyah (Journal Research of Social Science, Economics, and Management, 2026)
This study aims to determine the influence of career development and transformational leadership on employee performance at the Cirebon City Regional Disaster Management Agency. Employee performance is an important factor in improving work effectiveness and the quality of public services. This study uses d quantitative approach with a survey method. Data was obtained through the distribution of questionnaires to all BPBD employees with saturated sampling techniques. The data analysis method used is the Statistical Package for the Social Sciences (SPSS). The results of the study show that career development has a positive and significant effect on employee performance. Transformational leadership also has a positive and significant effect on employee performance. Simultaneously, career development and transformational leadership have a significant influence on employee performance. The results of this research are expected to be considered for agency leaders in improving employee performance through clear career management and the implementation of an effective leadership style.